If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1+3(x+2)=5(1+8x)
We simplify the equation to the form, which is simple to understand
-1+3(x+2)=5(1+8x)
Reorder the terms in parentheses
-1+(+3x+6)=5*(1+8x)
Remove unnecessary parentheses
-1+3x+6=+5+*(+1+8x+)
Reorder the terms in parentheses
-1+3x+6=+(+5+40x)
Remove unnecessary parentheses
-1+3x+6=+5+40x
We move all terms containing x to the left and all other terms to the right.
+3x-40x=+5+1-6
We simplify left and right side of the equation.
-37x=0
We divide both sides of the equation by -37 to get x.
x=-0
| -(2y-12+(-y))=-33 | | Y^4+y^3-4y-16=0 | | 5x+12=108-10x | | 1.3+-1.6= | | (4x)-(3x)+(2x)=24 | | 9+2j=5 | | 8m=7(7x-1) | | 18.84=2(3.14) | | 0.3(32)+x=0.3(20+x) | | 11x+45=2x | | (5-6i)(3-2i)=0 | | 3q+10=7 | | 7-(6x+2)=(x-12)+3 | | 2a+9=5a-6 | | x=18-2/3 | | 6+x=54 | | 67-39= | | 9.4=x-17 | | 2a+9=5a+6 | | .05x+.10(19-x)=1.55 | | 27=.9(200-a) | | 2x+3m-5x+7m= | | -3y-9=6y+18 | | x-11+-7= | | 36(x-25)=1620 | | 6x=7.8 | | 10-5-2x=-4x-7 | | 10h-10=10 | | 36xsquared=1 | | 3-4(4b-1)=10b+6 | | 2n+2=-298 | | Y=cosh(ln(x)) |